A spectroscopic analysis of the eclipsing nova-like EC 21178−5417 – discovery of spiral density structures. Issue 1 (13th March 2020) - Khangale, Z N; Woudt, P A; Potter, S B; Warner, B; Kilkenny, D; van der Heyden, K
ABSTRACT: We present phase-resolved optical spectroscopy of the eclipsing nova-like cataclysmic variable EC 21178−5417 obtained between 2002 and 2013. The average spectrum of EC 21178−5417 shows broad double-peaked emission lines from He ii 4686 Å (strongest feature) and the Balmer series. The high-excitation feature, C iii /N iii at 4640–4650 Å, is also present and appears broad in emission. A number of other lines, mostly He i, are clearly present in absorption and/or emission. The average spectrum of EC 21178−5417 taken at different months and years shows variability in spectral features, especially in the Balmer lines beyond Hγ, from pure line emission, mixed line absorption, and emission to pure absorption lines. Doppler maps of the He ii 4686 Å emission reveal the presence of a highly inclined asymmetric accretion disc and a two spiral arm-like structure, whereas that of the Balmer lines (Hα and Hβ) reveal a more circular accretion disc. There is no evidence of a bright-spot in the Doppler maps of EC 21178−5417 and no emission from the secondary star is seen in the tomograms of the He ii 4686 Å and Balmer lines. Generally, the emission in EC 21178−5417 is dominated by emission from the accretion disc. We conclude that EC 21178−5417 is a member of the RW Tri or UX UMa subtype of nova-like variables based on these results and because it shows different spectral characteristics at different dates. This spectral behaviour suggests that EC 21178−5417 undergoes distinct variations in mass transfer rate on the observed time-scales of months and years.